(3CQHYhf MOjKG ef WQb Cgd GdHjJ hGdhdGjIs - (3GdYGedj, GdMGQKj, GdgePGfj, HgGA GdOjf, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g`s
(3ChdgG (B:s
(3Ef CMSf MOjK JMdi GddSGf HLhGgQ MbGFbg(B... (3hHYO(B... (3Ef CYXe hGdeaGNQ HYO GdEjeGf HGddg hGdjhe GdBNQ(B...s
(3BNQgG (B:s
(3hgh efbhd aj GdcGaj hZjQg Yf CejQGdeDefjf hGdCFeI ef ChdGOg(B... (3hhGSWI Hjf GdYGdejf(B...s
(3JHUQI GdYfhGf (B:s
(3GdCQHYhf MOjKGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B102s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B251s
(3GdCYdGe(B: (3L(B6(3, U(B102s
Keywords: (3GdMOjK hGdeUWdMs